2019
DOI: 10.1021/acsomega.9b00937
|View full text |Cite
|
Sign up to set email alerts
|

Revert Banding in One-Dimensional Periodic Precipitation of the (AgNO3 + KBr) System in Agar Gel

Abstract: A periodically precipitating system wherein interband distance successively decreases is known as revert Liesegang banding. The phenomenon is rare, and the underlying mechanism is implicit. In the present paper, the Liesegang system comprising of AgNO 3 and KBr as the outer and inner electrolyte pair showing revert banding in agar gel by employing a 1D experimental setup is studied under varying concentrations of participating species. Revert banding was observed under all the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Because the concentration gradient of silver ions forms from x = 0, the barrier to the aggregation and precipitation decreases from x = 0, leading to the precipitated bands at increasingly closer distances, that is, revert Liesegang geometry. A similar revert geometry was observed for AgI [ 22 , 28 , 29 ] and AgBr [ 30 ] systems, whereas it has been reported that AgCl exhibited a regular geometry [ 31 ]. There appear to be two possibilities that could change the pattern geometry from the revert-type of AgI and AgBr to the regular-type of AgCl: (i) the difference in the concentration gradient of silver ions and (ii) differences in the preferential adsorption to the colloidal particles.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Because the concentration gradient of silver ions forms from x = 0, the barrier to the aggregation and precipitation decreases from x = 0, leading to the precipitated bands at increasingly closer distances, that is, revert Liesegang geometry. A similar revert geometry was observed for AgI [ 22 , 28 , 29 ] and AgBr [ 30 ] systems, whereas it has been reported that AgCl exhibited a regular geometry [ 31 ]. There appear to be two possibilities that could change the pattern geometry from the revert-type of AgI and AgBr to the regular-type of AgCl: (i) the difference in the concentration gradient of silver ions and (ii) differences in the preferential adsorption to the colloidal particles.…”
Section: Introductionsupporting
confidence: 78%
“…Materials that exhibit the revert pattern are mainly Pb [ 22 , 23 , 24 , 25 , 26 , 27 ] and Ag [ 22 , 28 , 29 , 30 ] salts. One of the proposed mechanisms to form the revert pattern in Pb and Ag systems is the preferential adsorption theory, in which the key factor that switches the pattern between regular and revert is the surface charge of colloidal particles, which are precursors of the precipitates [ 22 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The decreasing trend confirmed revert periodic precipitation. 32,33 RGB and Absorbance Values for Periodically Precipitating AgCl Systems. Figure 4A shows the image of banding of AgCl (formed via the chemical reaction AgNO 3 + KCl → AgCl ↓ + KNO 3 ) in the 1D Liesegang system when inner, outer, and gel concentrations were 0.05 M, 0.50 M, and 1% respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In PART-A, no specific trend is seen, whereas in PART-B, however, U values decrease with the band number, indicating explicit evidence for the revert banding in the present system. 32,33 It should be noted that the confirmation of revert banding based on U and Δx values may be erroneous as determination of the exact bandwidth is often tricky due to diffused band boundaries by the previous methods of distance analysis. Nevertheless, an evaluation of interband distance (Δx) and W can be done precisely using the present method.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation